2020
DOI: 10.1080/14735903.2020.1794490
|View full text |Cite
|
Sign up to set email alerts
|

Zero-tillage wheat provides stable yield and economic benefits under diverse growing season climates in the Eastern Indo-Gangetic Plains

Abstract: Zero-tillage wheat provides stable yield and economic benefits under diverse growing season climates in the Eastern Indo-Gangetic Plains,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Respondents also confirmed the existence of indirect benefits through CASI implementations. These indirect benefits link to both improved economic conditions through cash flow stabilization and increased resilience, a common finding with the increased economic opportunities and benefits that come from CASI implementation (Brown et al, 2021a) and improved lifestyles and financial stability (Keil et al, 2020). This may then be linked with an overall increased resilience in production systems.…”
Section: Discussionmentioning
confidence: 96%
“…Respondents also confirmed the existence of indirect benefits through CASI implementations. These indirect benefits link to both improved economic conditions through cash flow stabilization and increased resilience, a common finding with the increased economic opportunities and benefits that come from CASI implementation (Brown et al, 2021a) and improved lifestyles and financial stability (Keil et al, 2020). This may then be linked with an overall increased resilience in production systems.…”
Section: Discussionmentioning
confidence: 96%
“…The net benefit of ZT surpasses CT gross income by 11-17% [11]. Surveys encompassing farmers' fields adopting ZT wheat systems in India [22,31,34,48] show that those who opt for ZT planting of wheat following rice yield obvious economic and social perks. The children of the farmers get extra time for their study and sports activities.…”
Section: Cost Savings and Profitability Of Surface Seedingmentioning
confidence: 99%
“…In turn, progress in holistic wheat sector development will provide effective feedback into each of the components Accompanying technologies for irrigation and fertiliser usage are necessary to make best use of new seeds. For example, drawing on experience elsewhere, Keil et al (2020) showed that zero tillage methods resulted in significant yield gains and cost savings for wheat farmers in Bihar State, India. There is also evidence from Central Asia that the introduction of conservation agriculture techniques can improve sustainability of diversified cropping systems rather than focusing on single crop production (Boboev et al, 2019).…”
Section: Including Complementary Agricultural Servicesmentioning
confidence: 99%